PROFESSIONAL DEVELOPMENT OF THE UNIVERSITY LIBRARIANS (FROM EXPERIENCE OF THE SCIENTIFIC LIBRARY OF KRYVYI RIH PEDAGOGICAL INSTITUTE OF STATE HIGHER EDUCATION ESTABLISHMENT "KRYVYI RIH NATIONAL UNIVERSITY") - Kravchenko, Olena M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article dwells upon professional development experience of the librarians of Kryvyi Rih State Pedagogical Institute. The issues of continuous library education of higher education librarians are discussed.